Análise citopatológica do líquor em pacientes com leucemia linfoblástica aguda - Fraga, Thalyta Porto (2018)
Introduction: The Central Nervous System (CNS) is an important site of relapse in patients with Acute Lymphoblastic Leukemia (ALL), despite increasing cure rates in the last four decades in young patients. The presence of leukemic blasts in the Cerebrospinal Fluid (CSF) presents prognostic implication and therefore defines changes in the therapeutic protocol, which is why it requires diagnostic accuracy. The emergence of new techniques for identifying CSF leukemia blasts, such as flow cytometry and molecular methods, which are more costly and not uniformly accessible for clinical use, have led to the need to reassess the role of conventional cytology as diagnostic tool. Objectives: To identify the proportion of CSF samples positive for blasts in children and adolescents with ALL, using a standardized cytology technique and with standardization of variables related to the process that could interfere with the result. DESIGN: Prospective, descriptive, uncontrolled study in which samples of CSF obtained by lumbar puncture of patients with ALL that were starting treatment were examined. CSF samples were sent to the laboratory shortly after collection, being processed and cytocentrifugated in cytofunyl in up to four hours after collection. Four slides were prepared, stained and analyzed by a pathologist and a hematologist. RESULTS: Twenty-eight patients with ALL were evaluated, with predominance of male (58.6%), immunophenotype B (82.2%) and 78.5% were stratified as high risk for relapse. Of the 205 CSF samples evaluated, 26 (12.6%) were positive for blasts and among 28 patients, 11 (39.2%) had CSF with neoplastic infiltration. Comparing the groups with and without CNS infiltration, no statistically significant difference was observed for the variables analyzed. CONCLUSIONS: Conventional cytology was effective in the identification of CNS infiltration by blasts, provided there is a vigilance of factors related to collection, processing and analysis of CSF that may interfere in the reliability of the result.